Kecerdasan Emosional Kepala Sekolah dalam Meningkatkan Kompetensi Kepribadian Guru SMAN 11 Muaro Jambi - Hayatulisna. S; Jamilah Jamilah; Darma Putra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research uses a qualitative approach aimed at describing how the emotional intelligence of school principals improves teacher personality competence, to find out how teacher personality competence is and to find out the supporting and inhibiting factors in improving teacher personality competence with the emotional intelligence of school principals at SMAN 11 Muaro Jambi. The research findings indicate that the principal’s ability to recognize, manage, and express emotions effectively can create a conducive environment for the development of teacher personality. By providing motivational support, leading with empathy, and setting an example in interacting with teachers, the principal plays a role as an agent of change that enhances interpersonal relationships and teacher professionalism. Teacher personality competence is reflected in aspects of integrity and responsibility, emotional maturity, interpersonal skills, and strong commitment to the teaching profession. The main supporting factors for the principal's emotional intelligence in enhancing teacher personality competence include a conducive school environment, professional training and development, good role modeling by the principal, and social support among teachers. Meanwhile, significant inhibiting factors include limited time and resources, as well as teacher stress and workload. A principal with high emotional intelligence can play an essential role in creating positive change that supports the development of teacher personality, even though various challenges must be addressed.